EMPOWERMENT OF WOMEN VULNERABLE TO REPRODUCTIVE DISEASES IN MAJLIS TA'LIM AL-FARIZI COMMUNITY, SUKAMENTRI VILLAGE, GARUT CITY SUB-DISTRICT, GARUT REGENCY - Nasrullah, Yufi Mohammad; Munawaroh, Nenden; Usman, Asep Tutun; Fatonah, Nurul (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Technological changes and modernization in various sectors today are so rapid, that they affect human behavior in various ways. Technology on the one hand has a positive impact on people's lives, but on the other hand, technology also hurts society. Along with the development of technology, the need for plastic continues to increase. Plastic is also an artificial inorganic material composed of chemicals that are quite harmful to the environment and health. The purpose of this service is to increase the productivity skills of mothers in Sukamentri Village by providing safer bags made from nature to replace plastic items and utilize plastic waste with varied crafts. The method used is (Participatory Action Research) (PAR) is a research method carried out in a participatory manner among citizens in a lower-level community whose spirit is to encourage transformative actions to liberate society from the shackles of ideology and power relations (changes in better living conditions). The results of the Pangabdian activity were carried out well and received a positive response, this was seen from the enthusiasm of the participants by arriving on time, and the understanding of mothers about the dangers of using plastic waste increased. The increase in understanding is evidenced by the results of the pre-test before the delivery of the material and the post-test after the delivery of the material which shows the Mean with a result of 0.252 is positive, which means an increase after being given treatment. This activity is also aimed at improving the skills of mothers in processing waste waste, especially plastic waste with ecobrick techniques and minimizing the use of plastic for daily purposes. The resulting products are expected to improve the community's economy and provide positive activities for the group of mothers in Majlis Ta'lim Al-Farizi.